Development of Interactive Physics E-Book to Reduce Student Misconception - Pinandita Afriwardani; Jumadi Jumadi; Farchan Oktavianto Pribadi (Jurnal Penelitian Pendidikan IPA, 2023)
This research develops an interactive physics e-book to provide innovation in physics learning at schools. The purpose of the study was to determine the feasibility of a physics e-book on simple harmonic motion material, to determine the reduction of student misunderstandings after learning using e-books, and to determine the practicality of the e-books developed. This research uses research and development (R&D) methods with the research subjects of class X students. Based on learning innovations that have been carried out, it was concluded that e-book learning media has been developed to reduce student misunderstandings. E-book has been validated by 3 experts and the result are very good so it is suitable for use in learning. There is a reduction in student misunderstandings in modeling and implementation classes. The largest decrease occurred in the implementation class which was 11.00% while the modeling class was 9.00%. The e-books used successfully improved students' understanding by 18.00% in classroom modeling and 48.00% in implementation classes. The effectiveness of e-books in reducing student misconceptions belongs to the medium criteria in all classes. The practicality of e-books in modeling and implementation classes belongs to very good criteria.